Professional competence of school counselors in guidance and counseling services - Nadhirah, Nadia Aulia; Baiti, Luthvia Zahiro; Budiman, Nandang (Universitas Negeri Yogyakarta, 2024)
The professional competence of guidance and counseling teachers is an important aspect and affects the quality of guidance and counseling services provided by school counselor. As a guidance and counseling teacher, it is important and necessary to acquire professional competencies to facilitate the needs of students at school and to be able to provide the best service in helping students. The school counsellor profession is a job that is required special requirements so that in the implementation of the services provided can convince and gain the trust of those who need help. The professional competency standards of guidance and counseling teachers refer to whether they can master concepts, live and embody values, provide and demonstrate assistance, and professional performance of their responsibility. The research method used to achieve this goal is Systematic Literature Review (SLR). The results of some literature show that most guidance and counseling teachers have fulfilled professional competencies with high categories, this is shown by the guidance and counseling services provided in accordance with existing standards. However, this study also shows that some other guidance and counseling teachers are still in the medium and low categories. This affects the effectiveness of the services provided, so that guidance and counseling teachers need to improve their professional competence.